2014
DOI: 10.5301/ejo.5000426
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine in Patients with Retinal Vein Occlusion

Abstract: These results suggest that elevated fasting HCY levels, low vitamin B12 levels, and hypertension are associated with a risk of RVO, especially for CRVO. Moreover, our data suggest that only hypertension is associated with BRVO risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…According to some studies, plasma tHcy levels inversely relate to the plasma vitamin B12 and folate concentrations [9,25,26]. So, higher plasma levels of folate and vitamin B12 in patients may neutralize the tendency to elevated plasma tHcy levels, subsequently reducing the risk for endothelial damage and RVT development [5,27].…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies, plasma tHcy levels inversely relate to the plasma vitamin B12 and folate concentrations [9,25,26]. So, higher plasma levels of folate and vitamin B12 in patients may neutralize the tendency to elevated plasma tHcy levels, subsequently reducing the risk for endothelial damage and RVT development [5,27].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to neural degeneration, several retinal disorders have been associated with high levels of hcy. Elevated plasma hcy is a risk factor for retinal artery or vein occlusion, [11][12][13] and this condition is possibly improved by the intake of folate, vitamin B6, and vitamin B12 supplements, according to Martin et al 12 Hyperhomocysteinemia is also a main factor in the pathogenesis of retinal neuronal death, 14,15 diabetic retinopathy, 16 and even glaucoma. 17,18 However, the association between choroidal diseases and hcy levels has not yet been elucidated.…”
mentioning
confidence: 99%
“…Ocul Oncol Pathol 2020;6:159-163 DOI: 10.1159/000501155 A synergistic effect between coagulation disorders and the development of CRVO has been recognized; hypercoagulable workup can include testing for homocysteine and anticardiolipin antibodies, activated protein C resistance, and factor V Leiden testing [7][8][9]. A prospective case-control study found that patients with RVO were more likely to have hyperhomocysteinemia compared to controls [7], although some suggest that this is relevant to CRVO and not branch RVO [10]. Homocysteine is both atherogenic and prothrombotic and has been associated with a number of vascular events, including cerebrovascular, peripheral arterial, coronary heart disease, and venous thromboembolic disease [11,12].…”
Section: Discussionmentioning
confidence: 99%